Tracking Fluorescence-Labeled Rabies Virus: Enhanced Green Fluorescent Protein-Tagged Phosphoprotein P Supports Virus Gene Expression and Formation of Infectious Particles - Finke, Stefan (American Society for Microbiology, 2004)
Rhabdoviruses such as rabies virus (RV) encode only five multifunctional proteins accomplishing viral gene expression and virus formation. The viral phosphoprotein, P, is a structural component of the viral ribonucleoprotein (RNP) complex and an essential cofactor for the viral RNA-dependent RNA polymerase. We show here that RV P fused to enhanced green fluorescent protein (eGFP) can substitute for P throughout the viral life cycle, allowing fluorescence labeling and tracking of RV RNPs under live cell conditions. To first assess the functions of P fusion constructs, a recombinant RV lacking the P gene, SAD ΔP, was complemented in cell lines constitutively expressing eGFP-P or P-eGFP fusion proteins. P-eGFP supported the rapid accumulation of viral mRNAs but led to low infectious-virus titers, suggesting impairment of virus formation. In contrast, complementation with eGFP-P resulted in slower accumulation of mRNAs but similar infectious titers, suggesting interference with polymerase activity rather than with virus formation. Fluorescence microscopy allowed the detection of eGFP-P-labeled extracellular virus particles and tracking of cell binding and temperature-dependent internalization into intracellular vesicles. Recombinant RVs expressing eGFP-P or an eGFP-P mutant lacking the binding site for dynein light chain 1 (DLC1) instead of P were used to track interaction with cellular proteins. In cells expressing a DsRed-labeled DLC1, colocalization of DLC1 with eGFP-P but not with the mutant P was observed. Fluorescent labeling of RV RNPs will allow further dissection of virus entry, replication, and egress under live-cell conditions as well as cell interactions.